The contestations on the state of journalism in Zimbabwe between old school and contemporary journalists in Zimbabwe - Antonio, Terence (Midlands State University, 2018)
This study explores “old” school and contemporary journalist’s perceptions on the state of journalism in Zimbabwe. It interrogates the discourses around this emotive issue with a view to teasing out the biases and absences therein and how each group tries to legitimise itself at the expense of the other. The study is informed by van Dijk’s ideological square. In addition to the theory, the study utilised findings from numerous studies that spoke of declining standards on the state of journalism in Zimbabwe. The study located in the qualitative interpretive paradigm, selected its participants for interviews through purposive sampling. The data was subjected to critical discourse analysis. Findings of the study indicated that “old” school journalists attribute the decline of journalism standards in the country to unethical practice by contemporary journalists. The “old” school journalists accuse contemporary journalists for emphasizing on speed without accuracy, corruption, lack of objectivity and fuelling sensationalism. The young generation is also accused of lacking on agenda and poorly trained. To refute the allegations, contemporary journalists said the accusations of poor journalism are driven by jealousy. In typical legitimation strategy and scapegoating, both generations blame the post 2000 political and economic crisis as well as citizen journalists for contributing to the declining standards. It is anticipated that the findings of this study can be useful in going beyond simple binary comparisons of good vs bad journalism without giving practical incidences and reasons behind.